Thyroid function in preterm infants and neurodevelopment at 2 years. Issue 5 (20th February 2020) - Williams, Fiona L R; Lindgren, Alice; Watson, Jennifer; Boelen, Anita; Cheetham, Timothy
Abstract : Objectives: Postnatal thyroid dysfunction is common in preterm infants but the relationship between mild dysfunction and neurodevelopment is unclear. Our aim is to describe the relationship between thyroid function and neurodevelopment. Design: Cohort analysis. Patients: 1275 infants born under 31 weeks' gestation; there were no exclusion criteria. Setting: The infants were part of a UK daily iodine supplementation trial. Main outcomes: Thyroid-stimulating hormone, thyroid-binding globulin and total thyroxine levels were measured in dried blood spots on postnatal days 7, 14, 28 and the equivalent of 34 weeks' gestation. Neurodevelopment was measured using the Bayley-III Scales of infant development at 2 years of age. Results: No infant was identified as hypothyroid through routine screening. The 3% of infants consistently in the top decile of gestationally age-adjusted thyroid-stimulating hormone levels had a reduction in cognitive score of 7 Bayley units when compared with those not in the top decile (95% CI –13 to –1). A reduction in motor composite score of 6 units (95% CI −12 to <−0.1) and fine motor score of 1 unit (95% CI –2 to –0.1) was also identified. The 0.7% of infants consistently in the bottom decile of age-adjusted thyroxine levels had a reduction in motor composite score of 14 units (95% CI –25 to –2) and its two subset scores, fine and gross motor, of 2 units (95% CI respectively −4.5 to <−0.1 and –4.3 to –0.3). Conclusions: Preterm infants with consistent 'mild' thyroid dysfunction score less on neurodevelopmental tests at 2 years of age. Many of these infants will not be detected by current clinical protocols or screening programmes.